Novel SETBP1 mutation in a chinese family with intellectual disability - Le Wang; Xu-Dong Wang; Bo Yang; Xue-Meng Wang; Yu-Qian Peng; Hang-Jing Tan; Hong-Mei Xiao (BMC, 2023)
Abstract Background Intellectual disability (ID) is characterized by an IQ < 70, which implies below-average intellectual function and a lack of skills necessary for daily living. ID may occur due to multiple causes, such as metabolic, infectious, and chromosomal causes. ID affects approximately 1-3% of the population; however, the cause can be identified in only 25% of clinical patients. Methods To find the cause of genetic ID in a family, we performed whole-exome sequencing and Sanger sequencing to confirm the presence of a SETBP1 variant and real-time quantitative polymerase chain reaction to detect SETBP1 expression in the proband and normal controls. Results A novel variant, c.942_943insGT (p. Asp316TrpfsTer28), was found in SETBP1. Furthermore, we observed that SETBP1 expression in patients was only 20% that of normal controls (P < 0.05). Conclusion A heterozygous variant in SETBP1 associated with ID was found. This report provides further evidence for its genetic basis and support for clinical genetic diagnosis.